GREEN SUKUK KONTRIBUSI BAGI INVESTOR DAN PERUSAHAN PEMBANGUNAN BERKELANJUTAN MENUJU EKONOMI HIJAU - Ahmad Mu’is; Nasruddin Khalil Harahap; Misbah Mrd (Adpertens: Jurnal Ekonomi dan Manajemen, 2025)
This study evaluates whether investors are benefited by green sukuk by examining the stock return response to corporate green sukuk issuance announcements. Applying standard event study methodology, it is found that stock returns respond positively and significantly to green sukuk issuance announcements, indicating that investors perceive and react positively to the announcements. This significant positive response is observed both for individual firms (through CAR) and for the sample of all firms (through CAAR). Thus, it can be concluded that investors benefit from green sukuk issuance announcements. This study draws a comparative analysis of investor responses to corporate green sukuk and corporate green bond issuance announcements, and the findings also show that investors respond positively to green bond issuance announcements. However, investor responses are slightly higher to corporate green sukuk issuance announcements compared to corporate green bonds, and investors gain slightly more benefits from green sukuk issuance compared to green bond issuance. These findings inform policymakers for the formulation of strategies to attract investors by integrating green bonds with sharia principles to fund environmentally friendly projects and consequently reduce climate change risks.